Hypoxia mediated pulmonary edema: potential influence of oxidative stress, sympathetic activation and cerebral blood flow. Issue 1 (December 2015) - Khademi, Shadi; Frye, Melinda; Jeckel, Kimberly; Schroeder, Thies; Monnet, Eric; Irwin, Dave; Cole, Patricia; Bell, Christopher; Miller, Benjamin; Hamilton, Karyn
Abstract Background Neurogenic pulmonary edema (NPE) is a non-cardiogenic form of pulmonary edema that can occur consequent to central neurologic insults including stroke, traumatic brain injury, and seizure. NPE is a public health concern due to high morbidity and mortality, yet the mechanism(s) are unknown. We hypothesized that NPE, evoked by cerebral hypoxia in the presence of systemic normoxia, would be accompanied by sympathetic activation, oxidative stress, and compensatory antioxidant mechanisms. Methods Thirteen Walker hounds were assigned to cerebral hypoxia (SaO2  ~ 55 %) with systemic normoxia (SaO2  ~ 90 %) (CH;n  = 6), cerebral and systemic (global) hypoxia (SaO2  ~ 60 %) (GH;n  = 4), or cerebral and systemic normoxia (SaO2  ~ 90 %) (CON;n  = 3). Femoral venous (CH and CON) perfusate was delivered via cardiopulmonary bypass to the brain and GH was induced by FiO2  = 10 % to maintain the SaO2 at ~60 %. Lung wet to lung dry weight ratios (LWW/LDW) were assessed as an index of pulmonary edema in addition to hemodynamic measurements. Plasma catecholamines were measured as markers of sympathetic nervous system (SNS) activity. Total glutathione, protein carbonyls, and malondialdehyde were assessed as indicators of oxidative stress. Brain and lung compensatory antioxidants were measured with immunoblotting. Results Compared to CON, LWW/LDW and pulmonary artery pressure were greater in CH and GH. Expression of hemeoxygenase-1 in brain was higher in CH compared to GH and CON, despite no group differences in oxidative damage in any tissue. Catecholamines tended to be higher in CH and GH. Conclusion Cerebral hypoxia, with systemic normoxia, is not systematically associated with an increase in oxidative stress and compensatory antioxidant enzymes in lung, suggesting oxidative stress did not contribute to NPE in lung. However, increased SNS activity may play a role in the induction of NPE during hypoxia.